Breast cancer stem cells as last soldiers eluding therapeutic burn: A hard nut to crack. Issue 1 (16th August 2017) - Nilendu, Pritish; Kumar, Ajay; Kumar, Azad; Pal, Jayanta K.; Sharma, Nilesh Kumar
Abstract : Cancer stem cells (CSCs) are found in many cancer types, including breast carcinoma. Breast cancer stem cells (BCSCs) are considered as seed of cancer formation and they are associated with metastasis and genotoxic drug resistance. Several studies highlighted the presence of BCSCs in tumor microenvironment and they are accentuated with several carcinoma events including metastasis and resistance to genotoxic drugs and they also rebound after genotoxic burn. Stemness properties of a small population of cells in carcinoma have provided clues regarding the role of tumor microenvironment in tumor pathophysiology. Hence, insights in cancer stem cell biology with respect to molecular signaling, genetics and epigenetic behavior of CSCs have been used to modulate tumor drug resistance due to genotoxic drugs and signaling protein inhibitors. This review summarizes major scientific breakthroughs in understanding the contribution of BCSCs towards tumor's capability to endure destruction inflicted by molecular as well as genotoxic drugs.